Government actions for the Mennonites of a colony in Mexico - Cruz Cruz, Marisol (2018)
The aim of this research is the expose overnment actions to Mennonites in religion and economics. The document observes the public policy, as actions by the government to give economic life of society. Then the materials and methods, including review of other research, rescue information from a field journal of 391 pages, to understand the actions of the government with the Mennonite community. The findings on the government’s actions with religion and the Mennonite economy, remind us of their origin, their constant migration of Holland to Mexico, specific strategies designed to Mennonites by the government in Chihuahua lives with the Mennonites. It is a relationship of mutual benefit. Mennonites seek to preserve their faith and government economic dynamics.